The Act of Promise and Threat in Translated Verses of Law in The Qur'an - Nurul Chojimah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This study was aimed at finding the patterns of promise and threat in translated verses of law in the Qur’an and their syntactical realization.The data source for this research is the translated Qur’an published by the Ministry of Religious Affairs of the Republic of Indonesia. Data for this research are verses of law in marriage, inheritance, and trade containing the acts of promise and threat. The data were collected by reading and note-taking technique.The coding system by Blum- Kulka et al (1989) was adapted to analyze data for the study. It was found that the patterns of promise in translated verses of law can be classified into directive-commissive-conditional promise (DCCP), commissive-conditional promise (CCP), and neither-directive-nor-conditional promise (NDNCP). Directive-commissive-conditional threat (DCCT) is the only pattern of threat occurring in this study. Those speech acts are realized through conditional sentences and simple sentences. The conclusion is that the linguistic balance in the Qur’an can be found not only at the level of word and phrase, but also at the speech act level.